Early and Midterm Outcomes of Type II Hybrid Arch Repair for Complex Aortic Arch Pathology - Yanxiang Liu; Bowen Zhang; Shenghua Liang; Yaojun Dun; Hongwei Guo; Xiangyang Qian; Cuntao Yu; Xiaogang Sun (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThe hybrid arch repair (HAR) is an appealing surgical option in the management of aortic arch diseases. The aim is to evaluate the short and mid-term outcomes of type II HAR involving replacement of the ascending aorta, arch debranching, and zone 0 stent graft deployment in diverse arch pathologies.Methods200 patients with various diffuse aortic pathologies involving the arch were enrolled between 2016 and 2019. Complex arch diseases included acute type A dissection (n = 129, 64.5%), acute type B dissection (n = 16, 8.0%), aortic arch aneurysm (n = 42, 21.0%) and penetrating arch ulcer (n = 13, 6.5%). Mortality, morbidity, survival and re-intervention were analyzed.ResultsThe overall 30-day mortality rate was 8.0% (16/200). Stroke was present in 3.5% (7/200) of the general cohort and spinal cord injury was occurred in 3.0% (6/200). Multivariable logistic analysis showed that cardiac malperfusion and CPB time were the risk factors associated with 30-day mortality. The mean follow-up duration was 25.9 months (range 1–57.2 months), and the 3-year survival rate was 83.1%. On Cox regression analysis, age, diabetes, cardiac malperfusion and CPB time predicted short and mid-term overall mortality. A total of 3 patients required reintervention during the follow-up due to the thrombosis of epiaortic artificial vessels (n = 1), anastomotic leak at the site of the proximal ascending aorta (n = 1) and the type I endoleak (n = 1).ConclusionsType II HAR was performed with satisfactory early and mid-term outcomes in complex aortic arch pathologies.